Potensi Mikroorganisme Indigen Perairan Teluk Lampung sebagai Pendegradasi Masker Sekali Pakai (Disposable Face Mask) - Deviany, Deviany; Achmad, Feerzet; Purwanti, Millennia Rischa; Yudhanti, Tri Febri (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
To prevent the transmission of COVID-19, the World Health Organization recommends the implementation of health protocols including using disposable masks. The use of disposable face masks has an impact on the emergence of mask waste in aquatic environments which results in pollution of water sources by microfibers. Degradation by indigenous microorganisms can be one of the solutions for handling waste that is environmentally friendly and cost effective. In this study, bacteria were isolated from the coast of Lampung Bay which was polluted with plastic waste and masks. Bacterial isolates were characterized by morphological and biochemical tests before the selected one being used for degradation. After seven days of incubation, gravimetric analysis showed that the mask pieces increased in weight when compared to the control. However, the degradation process can be shown by the results of Scanning Electron Microscope (SEM) analysis which shows damage in the form of holes on the surface of the mask when compared to the new mask and the control. SEM images also showed the presence of bacterial biomass remnants attached to the surface of the mask. Based on the results of this study, Lampung Bay indigenous microorganism isolate showed potential as a degrader of disposable face masks.